Digital Activism in Asia Reader - Shah, Nishant; Purayil Sneha, Puthiya; Chattapadhyay, Sumandro (meson press, 2015)
The digital turn might as well be marked as an Asian turn. From flash-mobs in Taiwan to feminist mobilisations in India, from hybrid media strategies of Syrian activists to cultural protests in Thailand, we see the emergence of political acts that transform the citizen from being a beneficiary of change to becoming an agent of change. In co-shaping these changes, what the digital shall be used for, and what its consequences will be, are both up for speculation and negotiation. Digital Activism in Asia marks a particular shift where these questions are no longer being refracted through the ICT4D logic, or the West's attempts to save Asia from itself, but shaped by multiplicity, unevenness, and urgencies of digital sites and users in Asia. This reader crowd-sources critical tools, concepts, analyses, and annotations, self-identified by a network of change makers in Asia as important in their own practices within their own contexts.